Quantitative assessment of fibrosis and steatosis in liver biopsies from patients with chronic hepatitis C. Issue 6 (1st June 2001) - Zaitoun, A M; Al Mardini, H; Awad, S; Ukabam, S; Makadisi, S; Record, C O
Abstract : Backgrounds —Hepatic fibrosis is one of the main consequences of liver disease. Both fibrosis and steatosis may be seen in some patients with chronic hepatitis C and alcoholic liver disease (ALD). Aims —To quantitate fibrosis and steatosis by stereological and morphometric techniques in patients with chronic hepatitis C and compare the results with a control group of patients with ALD. In addition, to correlate the quantitative features of fibrosis with the Ishak modified histological score. Materials and methods— Needle liver biopsies from 86 patients with chronic hepatitis C and from 32 patients with alcoholic liver disease (disease controls) were analysed by stereological and morphometric analyses using the Prodit 5.2 system. Haematoxylin and eosin and Picro-Mallory stained sections were used. The area fractions (AA ) of fibrosis, steatosis, parenchyma, and other structures (bile duct and central vein areas) were assessed by stereological method. The mean diameters of fat globules were determined by morphometric analysis. Results —Significant differences were found in the AA of fibrosis, including fibrosis within portal tract areas, between chronic hepatitis C patients and those with ALD (mean (SD): 19.14 (10.59) v 15.97 (12.51)). Portal and periportal (zone 1) fibrosis was significantly higher (p = 0.00004) in patients with chronic hepatitis C compared with the control group (mean (SD): 9.04 (6.37) v 3.59 (3.16)). Pericentral fibrosis (zone 3) occurred in both groups but was significantly more pronounced in patients with ALD. These results correlate well with the modified Ishak scoring system. However, in patients with cirrhosis (stage 6) with chronic hepatitis C the AA of fibrosis varied between 20% and 74%. The diameter of fat globules was significantly lower in patients with hepatitis C (p = 0.00002) than the ALD group (mean (SD): 14.44 (3.45) v 18.4 (3.32)). Microglobules were more frequent in patients with chronic hepatitis C than in patients with ALD. In patients with chronic hepatitis C, the fat globules had a zonal distribution in comparison with pan steatosis in ALD. Conclusion —Quantitative, stereological techniques are simple and reliable for evaluating hepatic fibrosis and steatosis in chronic hepatitis C. They are most useful for assessing the origin, location, and the stage of fibrosis. Stereology and morphometry are recommended for the quantitation of fibrosis and steatosis, particularly for the evaluation of new treatment strategies in patients with chronic hepatitis C.